Heart failure and dementia: survival in relation to types of heart failure and different dementia disorders. (10th January 2015) - Cermakova, Pavla; Lund, Lars H.; Fereshtehnejad, Seyed‐Mohammad; Johnell, Kristina; Winblad, Bengt; Dahlström, Ulf; Eriksdotter, Maria; Religa, Dorota
<x xml:space="preserve">Abstract</x> Aims Heart failure (HF) and dementia frequently coexist, but little is known about their types, relationships to each other and prognosis. The aims were to (i) describe patients with HF and dementia, assess (ii) the proportion of specific dementia disorders in types of HF based on ejection fraction and (iii) the prognostic role of types of HF and dementia disorders. Methods and results The Swedish Heart Failure Registry (RiksSvikt) and The Swedish Dementia Registry (SveDem) were record‐linked. Associations between dementia disorders and HF types were assessed with multinomial logistic regression and survival was investigated with Kaplan–Meier analysis and multivariable Cox regression. We studied 775 patients found in both registries (55% men, mean age 82 years). Ejection fraction was preserved in 38% of patients, reduced in 34%, and missing in 28%. The proportions of dementia disorders were similar across HF types. Vascular dementia was the most common dementia disorder (36%), followed by other dementias (28%), mixed dementia (20%), and Alzheimer disease (16%). Over a mean follow‐up of 1.5 years, 76% of patients survived 1 year. We observed no significant differences in survival with regard to HF type (P = 0.2) or dementia disorder (P = 0.5). After adjustment for baseline covariates, neither HF types nor dementia disorders were independently associated with survival. Conclusions Heart failure with preserved ejection fraction was the most common HF type and vascular dementia was the most common dementia disorder. The proportions of dementia disorders were similar across HF types. Neither HF types nor specific dementia disorders were associated with survival.